Project Management in the Manufacturing of Custom Metal Products in Digital Marketplace Enterprises and Its Impact on Operational Efficiency: A Literature Review - Monika GÓRSKA; Marzena OGÓREK (Communications of International Proceedings, 2025)
The ongoing digitalization of the manufacturing sector is changing traditional approaches to project management, posing new challenges and at the same time requiring the adaptation of methodologies to dynamically developing business models. Despite the growing importance of digital marketplace platforms, there is a research gap in the literature regarding their impact on metal enterprises and the effectiveness of management processes in distributed production. This study aims to assess and analyze the developed and implemented principles and forms of cooperation during the implementation of projects with manufacturing partners and their impact on the functioning of the enterprise and its results. The study reviewed the literature on project management and the possibilities of implementing selected methodologies. In order to empirically verify the adopted assumptions, the ProGuide methodology was used, analyzing its implementation in the studied enterprise. The research results show that the integration of metal enterprises with the digital marketplace requires the adaptation of the project management strategy, which leads to increased operational efficiency and process optimization. The implementation of the ProGuide methodology supports the synchronization of activities and better allocation of resources. The article draws attention to the importance of further research on the digitalization of production and the need to adapt management tools to changing technological realities.
Keywords: digital marketplace; project management; forms of cooperation; ProGuide